The law as a conversation among equals / Roberto Gargarella. - Gargarella, Roberto, 1964- (Cambridge studies in constitutional law., 2022)
In a time of disenchantment with democracy, massive social protests and the 'erosion' of the system of checks and balances, this book proposes to reflect upon the main problems of our constitutional democracies from a particular regulative ideal: that of the conversation among equals. It examines the structural character of the current democratic crisis, and the way in which, from its origins, constitutions were built around a 'discomfort with democracy'. In this sense, the book critically explores the creation of different restraints upon majority rule and collective debate: constitutional rights that are presented as limits to (and not, fundamentally, as a product of) democratic debate; an elitist system of judicial review; a checks and balances scheme that discourages, rather than promotes, dialogue between the different branches of power; etc. Finally, the book proposes a dignified constitutional democracy aimed at enabling fraternal conversation within the framework of a community of equals.